Taking form - Borer, Hagit (Oxford University Press, 2013)
Ebook from Oxford Scholarship Online; Hagit Borer develops a new model of word formation, arguing that on the one hand the basic building blocks of language are rigid semantic and syntactic functions, while on the other hand they are roots, which in themselves are but packets of phonological information, and are devoid of both meaning and grammatical properties of any kind